Wettability of rock/CO2/brine systems: A critical review of influencing parameters and recent advances - Yekeen, N. (Korean Society of Industrial Engineering Chemistry, 2020)
Carbondioxide injection into geological formations is a promising method of optimizing hydrocarbon recovery, as well as improving CO2 geo-storage security. However, the success of CO2-enhanced hydrocarbon recovery and CO2 geo-storage projects is determined by the wettability of rock/CO2/brine systems. A critical review of the existing literature that discussed the wettability alteration of conventional and unconventional reservoir rocks (carbonate, sandstone and shale), as well as their representative pure minerals (calcite, quartz and mica), on interaction with CO2-water/brine system was conducted in this study. Wettability influencing parameters and recent advances in wettability modification by nanofluids/nano-surfactants were extensively discussed. Knowledge gaps were identified and direction for future studies were suggested. Â© 2020 The Korean Society of Industrial and Engineering Chemistry